Temperature dependence of ferromagnetic resonance spectra of permalloy on (Bi1−xSbx)2Te3. (27th December 2017) - Gupta, Sachin; Kanai, Shun; Matsukura, Fumihiro; Ohno, Hideo
Abstract: We investigate the temperature dependence of ferromagnetic resonance spectra of permalloy (Py: Ni0.80 Fe0.20 ) on (Bi1− x Sb x )2 Te3 with x = 0–1. Smaller resonance fields and broader linewidths are observed for Py/(Bi, Sb)2 Te3 than those for Py/substrate below ∼40 K. The result indicates the presence of the coupling as well as spin pumping at the interface between Py and (Bi, Sb)2 Te3 .